2020
DOI: 10.1007/s00401-020-02195-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma p-tau181 accurately predicts Alzheimer’s disease pathology at least 8 years prior to post-mortem and improves the clinical characterisation of cognitive decline

Abstract: The neuropathological confirmation of amyloid-β (Aβ) plaques and tau neurofibrillary tangles (NFT) remains the gold standard for a definitive diagnosis of Alzheimer's disease (AD). Nowadays, the in vivo diagnosis of AD is greatly aided by both cerebrospinal fluid (CSF) and positron emission tomography (PET) biomarkers. Although highly accurate, their broad implementation is restricted by high cost, limited accessibility and invasiveness. We recently developed a high-performance, ultrasensitive immunoassay for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
226
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 249 publications
(246 citation statements)
references
References 31 publications
19
226
0
1
Order By: Relevance
“…Our < 65-year plasma NfL cut-offs (19.4 pg/mL, 21.5 pg/mL, 30.0 pg/mL) were substantially lower as to compared older cut-offs (38.0 pg/mL, 46.0 pg/mL, 54.8 pg/mL) and when this was applied, EOAD patients had the equivalent rate of abnormal plasma NfL as typical AD dementia -consistent with the reported literature on familial AD 56,57 . We also observed that age-related cut-offs may be more sensitive to neurodegeneration related to Aβ deposition, although it is clear that recent developments in plasma p-tau181 or p-tau217 would be a superior measure of Aβ and tau pathologies 10,11,14,15,51,58 . In individuals < 65 years, rates of abnormal plasma NfL were 3-fold higher in Aβ + controls as compared to Aβ-controls and also higher in MCI Aβ + than MCI Aβ-.…”
Section: Discussionmentioning
confidence: 75%
“…Our < 65-year plasma NfL cut-offs (19.4 pg/mL, 21.5 pg/mL, 30.0 pg/mL) were substantially lower as to compared older cut-offs (38.0 pg/mL, 46.0 pg/mL, 54.8 pg/mL) and when this was applied, EOAD patients had the equivalent rate of abnormal plasma NfL as typical AD dementia -consistent with the reported literature on familial AD 56,57 . We also observed that age-related cut-offs may be more sensitive to neurodegeneration related to Aβ deposition, although it is clear that recent developments in plasma p-tau181 or p-tau217 would be a superior measure of Aβ and tau pathologies 10,11,14,15,51,58 . In individuals < 65 years, rates of abnormal plasma NfL were 3-fold higher in Aβ + controls as compared to Aβ-controls and also higher in MCI Aβ + than MCI Aβ-.…”
Section: Discussionmentioning
confidence: 75%
“…Most data currently available suggest that P-tau217 is earlier and more strongly associated with AD pathology than plasma P-tau181 [ 47 , 48 ], but more head-to-head comparisons are needed before a conclusion can be reached. As an example, while plasma P-tau217 measured by the ECL immunoassay showed an AUC of 0.89 to differentiate neuropathologically defined AD from non-AD in blood samples taken during life in one cohort [ 47 ], the corresponding number for plasma P-tau181 measured using Single molecule array (Simoa™) was 0.97 in another [ 49 ]. These findings call for further studies comparing different P-tau biomarkers in the same cohort.…”
Section: Biomarkers For Tau Pathologymentioning
confidence: 99%
“…Results from Karikari et al [ 3 ] indicate that plasma p-tau181 increases during early stages of tau pathology accumulation, but reaches a plateau in cases with moderate to severe pathology. In agreement, the performance of plasma p-tau to identify AD pathology is very high in later disease stages [ 7 ]. In view of these results, one could hypothesize that genetic risk factors for AD, especially those with smaller effect than APOE , are of greater importance in relation to p-tau181 during the time when the level of the biomarker changes the most.…”
Section: Discussionmentioning
confidence: 75%
“…This indicates that having MCI and being Aβ-positive is the most vulnerable combination in relation to the association between genetic risk for AD beyond APOE and plasma p-tau181. Previous studies have shown that p-tau181 increases already in response to Aβ pathology and then further in a stepwise manner with more advanced Braak stage [ 3 5 , 7 ]. P-tau181 signaling already in response to Aβ positivity is in line with our results for the non- APOE PRSs (i.e., association with ptau181 in MCI and Aβ positive individuals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation